E-Government Framework for the Information Disclosure Sector in the East Java Regional Government through a Socio-Technological Approach - Moch. Helmi Zirey Pratama; Eny Haryati (Utan Kayu Publishing, 2025)
The rapid development of Information and Communication Technology (ICT) has driven a revolution in the government sector, triggering a shift from conventional systems to E-Government. E-Government in the East Java regional government aims to accelerate population services, licensing, and public policy information. However, fundamental obstacles include selfish sectoral initiatives, a lack of effective management systems and work processes, and a limited focus on website implementation. This study aims to produce a conceptual design for web-based E-Government development, with the objectives of mapping driving and inhibiting factors, evaluating websites, preparing blueprints, formulating development, and recommending E-Government models to realize Smart Cities. Qualitative research methods involved interviews, focus groups, and discussions with informants from various levels of government and society. The level of technological readiness in this research is at level 2 (two), which seeks to formulate a conceptual design for an E-Government Development model in realizing a Smart City in the East Java Provincial Government and to recommend an E-Government Development model in realizing a Smart City in the East Java Provincial Government. The outputs and targets of this research are reputable international journals and policy briefs.